2015
DOI: 10.1016/j.joca.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular administration of xenogeneic neonatal Mesenchymal Stromal Cells early after meniscal injury down-regulates metalloproteinase gene expression in synovium and prevents cartilage degradation in a rabbit model of osteoarthritis

Abstract: Early IA injection of equine UC-MSC was effective in preventing OA signs in rabbit knees following MMR. UC-MSC target the synovium and modulate the gene expression pattern of synoviocytes to promote an anti-catabolic environment. This confirms the synovium is a major target and mediator of MSC therapy, modulating the expression of matrix-degrading enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 34 publications
(34 reference statements)
2
67
0
Order By: Relevance
“…However, in our study we observed lymphoplasmacytic infiltration and inflammation in both cohorts. Our findings are consistent with other studies showing immune responses related to xenogeneic transplantation [] and nonautologous transplantation of isolated cells [, ]. It appears there is no consensus on the biological effects of heterologous cell transplantation in rabbits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in our study we observed lymphoplasmacytic infiltration and inflammation in both cohorts. Our findings are consistent with other studies showing immune responses related to xenogeneic transplantation [] and nonautologous transplantation of isolated cells [, ]. It appears there is no consensus on the biological effects of heterologous cell transplantation in rabbits.…”
Section: Discussionsupporting
confidence: 92%
“…Histologic evaluation of tissues did reveal a higher incidence of cellular infiltration in knees receiving AMSC therapy. The latter response has been observed in previous animal models of OA and/or MSC studies [], but it did not translate into evidence of major structural damage to cartilage or other intrasynovial tissues, as evident from the OARSI scoring for articular cartilage or synoviopathy.…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, the expression of anti‐Calcitonin Gene‐Related Peptide in the C5 dorsal horn of the OA animals was also significantly decreased, indicating a suppressive effect on the central sensitization component of pain. Saulnier et al confirmed the reduced expression of metalloproteinases (1, 3, and 13) after MSC injection, but describe that MSC‐conditioned medium can also convey these anti‐inflammatory effects on OA synoviocytes. In sum, MSC treatments are known to induce potent anti‐inflammatory, tissue‐restoring, and analgesic effects that could explain the clinical findings described in recent trials as well as in the present phase I/II study.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs generate a local immunosuppressive microenvironment by secreting cytokines (19). In addition to immunomodulatory functions, MSCs secrete trophic and soluble factors that reduce synovial inflammation, exert anti-catabolic effects, and recruit endogenous MSCs in the joint environment (2023). Taken together, these pleiotropic actions justify an evaluation of the extent to which the local administration of MSCs compares to NSAIDs in managing postoperative joint pain in dogs (24).…”
Section: Introductionmentioning
confidence: 99%